Central African Economic and Monetary Community (CEMAC) : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides detailed assessment of the Central African Economic and Monetary Community's (CEMAC's) financial system. Over the past decade, primarily as a result of high oil prices, CEMAC achieved robust economic growth, although lower than the SSA average, but insufficient to significantly reduce poverty. A poor business climate and weak governance are hampering financial sector development and its contribution to financing investments. The weakness of regional integration also limits the growth potential. The drop in oil prices by about 60 percent between June 2014 and January 2015 has had a large impact on CEMAC countries' macroeconomic performance.